A comprehensive review on microchannel heat sinks for electronics cooling - Zhi-Qiang Yu; Mo-Tong Li; Bing-Yang Cao (International Journal of Extreme Manufacturing, 2024)
The heat generation of electronic devices is increasing dramatically, which causes a serious bottleneck in the thermal management of electronics, and overheating will result in performance deterioration and even device damage. With the development of micro-machining technologies, the microchannel heat sink (MCHS) has become one of the best ways to remove the considerable amount of heat generated by high-power electronics. It has the advantages of large specific surface area, small size, coolant saving and high heat transfer coefficient. This paper comprehensively takes an overview of the research progress in MCHSs and generalizes the hotspots and bottlenecks of this area. The heat transfer mechanisms and performances of different channel structures, coolants, channel materials and some other influencing factors are reviewed. Additionally, this paper classifies the heat transfer enhancement technology and reviews the related studies on both the single-phase and phase-change flow and heat transfer. The comprehensive review is expected to provide a theoretical reference and technical guidance for further research and application of MCHSs in the future.